STRATEGI DINAS KEBUDAYAAN DAN PARIWISATA DALAM MENGEMBANGKAN DESA WISATA DI KOTA PEKANBARU - Adinda Qori T.M; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to explain the strategy of Pekanbaru city government through the Department of Culture and Tourism in developing a tourist village in Pekanbaru City. Pekanbaru City Government has launched several villages as a tourist village in accordance with the Decree of the Head of Culture and Tourism Office No. 84 of 2010.In this study the authors use strategy theory. To bridge the theory to the strategy of the culture and tourism office of Pekanbaru city in developing the tourist village the author uses the frame of mind refers to the view of Higgins called Master Strategy. In his view the strategy theory in developing the tourist village will consider aspects of enterprise strategy, corporate strategy, business strategy and functional strategy.City of culture and tourism office Pekanbaru designing four urban villages that will become the tourist object. Pekanbaru Municipal Government through the Department of Culture and Tourism together the community to form a tourism conscious group (POKDARWIS) and directly guided by the Head of Culture and Tourism and members of the local community.Keywords: Strategy, Tourism Village, Department of Culture and Tourism Pekanbaru City